เครือข่ายทางสังคมและระบบดัชนีสุขภาพโรงเรียนในฐานะตัวแทรกแซงที่ส่งเสริมสุขภาวะของนักเรียนในโรงเรียนส่งเสริมสุขภาพ - ขวัญเมือง แก้วดำเกิง (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research was designed on mixed methods with 3 objectives: (1) To study the relationships among the variable of school characteristics and the variables of social network and health services management according to the school health index system (2) To study the relationships between the variables of school characteristics, social network and the school health index system and the variable of students well-being and (3) To compare social networks in health promoting schools. The research was divided into 3 phases: Phase 1-development of the school health index system; Phase 2-exploration and study of the relationships among school characteristics, social network and school health index system and student well-being in health promoting schools and; Phase 3- a case study of social network in health promoting schools. The multi-stage sample consisted of 247 schools: secondary schools under the supervision of the Office of the Basic Education Commission, the Office of the Private Education Commission and the Bureau of Local Education Administration in Nonthaburi, Suphanburi, Rayong, Kanchanaburi and Bangkok and a sample group of health networks from schools selected for the case study for a total of 181 people. Data analysis included descriptive statistics, Pearson s product moment correlation, ANOVA using SPSS 11.5 and analyses of structural model using LISREL 8.7 and social network analyses using UCINET and NetDraw programs and analyses of qualitative data using content analysis. The findings: (1) In terms of the relationships among the variables, it was found that social network was significantly associated with school health index system and significantly associated with student well-being. Furthermore, school health index system was significantly associated with student well-being. (2) School characteristic variables comprised the following: (a) school sector was not significantly associated with social network, school health index system or student well-being. (b) school size was significantly associated with school health index system, but was not significantly associated with social network and student well-being and (c) teacher ratio was significantly associated with social network and school health index system but was not significantly associated with student well-being. (3) Student well-being was directly affected by social network with a score of 0.18 and indirectly affected through the school health index system with a score of 0.24. Student well-being was directly affected by the school health index system with a score of 0.35 (4) The validation results of the structural model for health promotion in secondary school students, it was found that the model fit nicely with the empirical data (chi-square=114.64, df=94, p=0.07, GFI=0.948, AGFI=0.915, RMR=0.051). (5) The results of comparison of means of student well-being or school health index system with different social network (structure, functional and interaction) it was found that the student well-being has effects from interaction between structure and interaction but the school health index system has no retrieve effects from interaction. (6) According to the egocentric and whole-network analyzing indicated that the schools which different with quality of School health index system they were different social network. (7) By the comparison of social networks of schools with differing school health index systems, it was found that network size, centralization, and clustering can be used to categorize schools with diverse good health service management according to the school health index system. The density of the network and eigenvector centrality cannot be clearly categorized.